The nutrition transition and prevention of diet-related chronic diseases in Asia and the Pacific - Popkin, Barry M.; Horton, Susan; Kim, Soowon (Asian Development Bank, 2001)
This work was carried out as part of the ADB-IFPRI Regional Technical Assistance Project on Nutrition Trends, Policies and Strategies in Asia and the Pacific. Chronic diseases may soon dominate the disease burden of Asia and the Pacific - at much higher cost to families and health systems than infectious diseases.